Complete mitogenome of Calliptamus barbarus Costa (Orthoptera: Acrididae) and its phylogeny in Acridoidea - Ding, Xunhuan; Fu, Yun; Zhou, Xuan; Yang, Shubing; Cao, Yunmeng; Hou, Fuxiao; Liu, Xiaoli; Sun, Tao (Zootaxa, 2022)
Calliptamus barbarus Costa is a species in genus Calliptamus, belonging to the Calliptaminae, Acrididae, Orthoptera. In the present study, the mitogenome of C. barbarous was determined and annotated to better identify C. barbarous and other related species. The mitogenome was 15,686 bp in length and encoded 37 genes, including 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes and a control region. The nucleotide composition analysis of the mitogenome showed a strong bias of A/T, with A+T content of 72.7%, being similar to other reported mitogenomes. All the 13-PCGs used typical start codons of ATN and stop codons of TAA/G. All of the transfer RNA genes had typical clover-leaf structure except the missing dihydrouidine (DHU) arm of tRNASer1. Interestingly, we observed two overlapped but conserved regions between ATP8 and ATP6 genes, ND4 and ND4L genes. The results of Ka/Ks implied that CytB is more conservative than COX1. Phylogenetic analyses based on the 13-PCGs from 30 species indicated strong support for the monophyly of Acridoidea and represented the main topology as follows: (Oedipodinae+ (Acridinae+ (Gomphocerinae +((Calliptaminae+Catantopinae) +(Oxyinae+Melanoplinae))))). The phylogenetic relationship indicated that the molecular taxonomy of C. barbarous was consistent with the current morphological classification. The data in the present study will further enrich the mitogenome database of Acridoidea and provided useful clues for further research of C. barbarous on the mitogenome evolution and diversification of Calliptamus.